KEEFEKTIFAN MEDIA MATEMATIKA VIRTUAL BERBASIS TEAMS GAME TOURNAMENT DITINJAU DARI COGNITIVE LOAD THEORY - Nuryadi, Nuryadi (AlphaMath : Journal of Mathematics Education, 2018)
The purpose of this study is to produce virtual mathematics learningmedia based on good quality of TGT for use in learning mathematics and describe how well the mathematics learning tools quality which was produced. The quality criteria used refers to the Nieveen criteria, which are valid, practical and effective. The material that was developed was the material of plane geometry. This research developed a mathematics learning tool using a development model adapted from the ADDIE development model. The stages that need to be done to obtain a valid, practical and effective multimedia learning mathematics is requirement analysis and objective formulation, product design / development, trial, revision and final product study. The experiments included expert trial / expert judgment, small group try-out and field try-out. The field try-out was done on two classes of VIII grade in SMP N 1 Sedayu. The research instrument used was validation sheet, teacher's appraisal sheet, student assessment sheet, and Cognitive Load Theory (CLT) test. This research produces a qualified and viable virtual mathematics learning media. The results showed that multimedia learning mathematics which was developed is valid, practical and effective.